The Company’s Internal Characteristics and Mandatory Disclosure Size of Web-Based Financial Reporting - Weli Weli (Universitas Hayam Wuruk Perbanas, 2016)
The new regulation on the Indonesian Capital Market (XK6-Bapepam-LK No. KEP-431/BL/ 2012), related to the disclosure of financial information on the company's website is the main motivation of this study, which is to analyze the extent to which issuers responded to the new regulation. The study was conducted on 50 companies included in the list of 50 companies with the highest score of corporate governance version IICD in 2013 - 2014 and 57 companies in the same industry as a control companies, with the total number of samples is 107 companies. The study was conducted by analyzing the factors (size, listing period, industry, the quality of corporate governance) that affect the level of disclosure by the company on their website. The results showed that not all sample companies do a full disclosure and the average disclosure is only 77%. Further, the factor of disclosure size was also influenced by the company's internal characteristics such as company size, type of industry and good corporate governance.